2021
DOI: 10.18203/2349-2902.isj20211845
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative use of Lugol’s iodine in a case with toxic adenomatous goiter

Abstract: Euthyroid state is considered a requisite before planning a thyroid surgery. Before such a surgery, pharmacotherapy can be used for managing a hyperthyroid state. It warrants a long-term treatment with pharmacotherapy agents like imidazole class (carbimazole, methimazole) or propylthiouracil. In cases with large goiters, with pressure symptoms like dyspnoea, dysphagia, dysphonia; a surgeon would prefer a pharmacotherapy with a quicker action than the established agents. Lugol’s iodine was used pre-operatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Ten kinds of literature were found involving adult patients aged >25 years with quite diverse thyroid disorders such as toxic adenoma, psychosis, autoimmune thyroid, and thyroid papillary cancer. Clinical manifestations, as in Table 1, generally show clinical symptoms such as swelling of the thyroid gland, difficulty breathing, progressive weight gain, tremors, and palpitations 9,13,14 . Researchers also found manifestations that appear in visual disturbances, namely pain in the eye area, conjunctival hyperemia, swollen eyelids, reduced visual acuity (6/18), and reduced color vision; this condition is related to thyroid eye disease 16 .…”
Section: Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten kinds of literature were found involving adult patients aged >25 years with quite diverse thyroid disorders such as toxic adenoma, psychosis, autoimmune thyroid, and thyroid papillary cancer. Clinical manifestations, as in Table 1, generally show clinical symptoms such as swelling of the thyroid gland, difficulty breathing, progressive weight gain, tremors, and palpitations 9,13,14 . Researchers also found manifestations that appear in visual disturbances, namely pain in the eye area, conjunctival hyperemia, swollen eyelids, reduced visual acuity (6/18), and reduced color vision; this condition is related to thyroid eye disease 16 .…”
Section: Manifestationsmentioning
confidence: 99%
“…Previous studies have also shown that all three treatment methods (anti-thyroid medications, radioactive iodine, and surgery) show good results on the long-term quality of life of patients 28 . In some cases, anti-thyroid medication is most commonly given in patients with toxic adenoma, psychosis, fetal hyperthyroidism, fetal goiter, autoimmune, thyroid eye disease, and anxiety disorders 2,9,10,13,16,18 . Anti-thyroid medications that are widely used in the findings of the cases discussed are methimazole with varying doses of 0.5mg to 30mg/kg/day.…”
Section: Treatmentsmentioning
confidence: 99%